Solving Method for the Tooth Mesh Stiffness based on Transmission3D - Weixia Li; Tao Zhang (Jixie chuandong)
A method is proposed to calculate the tooth meshing stiffness based on Transmission3D （T3D）. FE/CM model is built to ensure the solving accuracy and efficiency. By using this method， the time-varying meshing stiffness and average value of a spur gear pair are both calculated， and the difference is 2.6% compared with the value solved by ISO 6336—1996， the rationality of the solution method is proved. Aiming at the deficiency of existing standards， the influence of shaft hole radius on the meshing stiffness is analyzed based on T3D and the mechanism is discussed combing the general FE method. On this basis， the meshing stiffness treatment method for the dynamics modeling and modal analysis of the aero-gear system is given.